138k views
2 votes
F(x)=43

f(x)=-6×+7

Not sure how to get the answer wondering if someone can break it down for me please

User Don Vince
by
5.1k points

2 Answers

6 votes
set them equal to eachother to solve for x
43=-6x+7
36=-6x
-6=x
User DIRTY DAVE
by
5.1k points
2 votes

Explanation:

Since f(x) is 43 you would replace it for the f(x) in the bottom equation like this 43=-6×+7 then you would multiply the left side so now it would be 43=-42 and this a no solution.

User Matt Camp
by
5.7k points